Analysis Of The Main Approaches Used To Improve The Learning Process - A.SH.Akhmedova (Euro Asian Journal Publishing, 2024)
This study explores key approaches to enhancing educational processes through modern pedagogical strategies, technological integration, and policy development. Methods such as STEM, competency-based education, and Bloom’s Taxonomy were analyzed for their impact on student engagement, critical thinking, and practical skill development. The study employed a multimethod approach, including literature reviews, comparative analysis, case studies, surveys, expert interviews, and experimental methods, to provide a comprehensive understanding of these approaches. Results indicate that innovative methods significantly improve learning outcomes but require proper teacher training, resource availability, and cultural adaptability. Digital tools such as Learning Management Systems (LMS) and AI platforms were found to enhance personalization and interactivity but face challenges due to the digital divide. The findings emphasize the need for global collaboration and localized adaptations to ensure equitable and inclusive education. By aligning innovative practices with international frameworks and addressing local challenges, education systems can better prepare students for the demands of the 21st century
Keywords: Educational processes; pedagogical strategies; STEM education